PENENTUAN pH DAN SUHU OPTIMUM UNTUK AKTIVITAS EKSTRAK KASAR ENZIM LIPASE DARI KECAMBAH BIJI KARET (Hevea brasiliensis) TERHADAP HIDROLISIS PKO (Palm Kernel Oil) - Rizki Amalia Nasution (USU, 2013)
Abstract Determination of optimum pH and temperature for crude lipase enzyme activity from rubber seeds germination had been conducted. Rubber seed germination made by soaking time process, seed separation with shell’s and seed germination in temperature 27-30oC during 6 days. Crude lipase enzyme was obtained by two times centrifugations with the speed of rotation at 5000 rpm and 10000 rpm during 30 minutes by additing aceton 70%. The crude enzyme is diluted with phosfat buffer pH 7,0. The activity test of crude lipase enzyme is done by measurement of free fatty acid levels is obtained from hydrolisis process of PKO as subtrate by titrimetric method at temperature variation 40; 45; 50; 55; 60oC and pH 6,0; 6,5; 7,0; 7,5; 8,0. The result shower that the highest activity is 2,432 U/mL at pH optimum 7,0 and temperature optimum 40oC. Keywords : pH, Temperature, Activity, Lipase, Rubber Seed.